Graphic design thinking : Beyond brainstorming. - Lupton, Ellen, 1963- (New York : Princeton Architectural Press, 2011)
Creativity is more than an inborn talent. It is a hard-earned skill that, like all skills, improves with practice. Graphic Design Thinking explores a variety of techniques-from quick, seat-of-the-pants approaches to more formal research methods-for stimulating fresh thinking and solving design problems. Brainstorming techniques are grouped around the three main phases of the design process: defining problems, getting ideas, and creating form. Visual demonstrations and case studies show the design processes and solutions at work.
Keywords: Grafische kunst; Grafische technieken; Grafische vormgeving